2021
DOI: 10.1111/ajo.13335
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term cardiovascular impact of hypertension in pregnancy – A missed opportunity

Abstract: Women who have had hypertension in pregnancy, both pre-eclampsia and gestational hypertension, have a two-to three-fold increased risk of cardiovascular disease later in life. It is unclear whether this is an unmasking of latent risk, the result of damage to the vascular tree during pregnancy, or both. Irrespective of the underlying pathophysiology, these women are uniquely identified sufficiently early in their lives for lifestyle interventions, if adopted, to improve their long-term health. Currently, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The uterine spiral artery has not experienced the changes of normal pregnancy, but still maintains the sensitivity to vasoconstrictive substances and relatively narrow diameter. This will lead to shallow placenta implantation than normal pregnancy, decreased blood perfusion, and a series of clinical symptoms of HDCP [ 21 ]. The increase of blood pressure after pregnancy will lead to the damage of vascular endothelium and the release of endogenous vasodilator factor, vasodilator factor, and NO.…”
Section: Discussionmentioning
confidence: 99%
“…The uterine spiral artery has not experienced the changes of normal pregnancy, but still maintains the sensitivity to vasoconstrictive substances and relatively narrow diameter. This will lead to shallow placenta implantation than normal pregnancy, decreased blood perfusion, and a series of clinical symptoms of HDCP [ 21 ]. The increase of blood pressure after pregnancy will lead to the damage of vascular endothelium and the release of endogenous vasodilator factor, vasodilator factor, and NO.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several in Groups 2 and 3 who visited the clinicians at six months clearly absorbed the significance of the condition for their future health, and two described the revelation as a “wake-up call” (M01 and M10). This finding has implications not only for future interventions, but for general antenatal, birthing and primary health services that have not, to date, conveyed the seriousness of HDP for women’s ongoing health [ 18 ]. This may be particularly important for women who experienced fewer HDP complications, with prior research demonstrating better risk perception among women with severe disease or whose infants were born preterm [ 31 ], and among those with a family history of CVD [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the established link with subsequent CVD, there is limited evidence from interventions aimed at women following HDP [ 16 ]. Moreover, Australian women have limited knowledge of how to maintain health after HDP [ 13 , 17 ] and follow-up programs are inadequate in helping them address risk factors and adopt healthier lifestyles [ 18 ]. Previous studies have identified that participants were generally eager to increase their understanding of HDP, and several expressed interest in lifestyle interventions to reduce their risk of future HDP and ongoing CVD [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite awareness about HDP women continue to develop complications/die as a result of hypertension more so in low and middle income countries (LMIC). 2 Evidence is building to suggest that lifestyle interventions are useful in reducing the risk of cardiovascular disease in women whose pregnancy was complicated by hypertension. 3 Consensus on diagnostic criteria, classification of HDP, when to treat hypertension in pregnancy and timing of delivery has been difficult to achieve.…”
Section: Overview and Guideline Development Methodologymentioning
confidence: 99%